Experimental study on flexural performance of steel-reinforced concrete slim floor beams. Issue 11 (August 2019) - Yu, Yunlong; Wei, Bo; Yang, Yong; Xue, Yicong; Xue, Hao
In long-span floors, the use of composite slim floor beams can effectively improve the flexural stiffness and flexural capacity of the floor system. In order to strengthen the stiffness of the composite slim floor beams and achieve better fire resistance, an innovative steel-reinforced concrete slim floor beams is presented in this article. To investigate the flexural performance of the steel-reinforced concrete slim floor beams, static loading experiments were carried out on six specimens. The parameters of the test were the height of slim floor beams and the type and size of steel shape in the steel-reinforced concrete slim floor beams. On the basis of the experiment, the bending failure modes, flexural stiffness, and flexural capacity of the steel-reinforced concrete slim floor beams were studied comprehensively. The test results indicated that the steel-reinforced concrete slim floor beams exhibited great flexural capacity, large stiffness, and high ductility. The calculation formulas of flexural stiffness and flexural capacity were also proposed in this article. The analysis of flexural performance of the steel-reinforced concrete slim floor beams can provide a significant foundation for further research.